L’apport de l’identification des théories d’action dans l’évaluation des politiques publiques de paysage des documents d’urbanisme - Didier Labat (Projets de Paysage, 2009)
The urban plans include lanscape public policies that have to be assessed to know their efficiency and their relevance. The public policies assessment requires methods that we suggest to adapt to the urban plans and to the landscape policies in particular. Among the different stages of this assessment, the action theories identification is a canvass that we have tested on Bordeaux’s metropolitan urban plan. Using this method, it appears that, the content of a landscape policy can be precisely identified, and it is easier to check its consistency and its relevance. It is also easier to point out the most efficient orientations and the ways the actors proceed.